The effects of hot-deboning on the physical quality characteristics of ostrich (Struthio camelus) Muscularis gastrocnemius, pars interna and Muscularis iliofibularis - Botha, Sune St.Clair (Stellenbosch : University of Stellenbosch, 2006)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2005.